ANALISIS KAMPANYE SOSIAL PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM KAMPUNG PANGAN INOVATIF YANG DISELENGGARAKAN PT KPI RU III PLAJU KOTA PALEMBANG - Eva Kurnia, Siti Rachmi Indahsari, Binsar Butar-Butar (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2022)
Social campaigns are a series of non-commercial planned communication processes within a certain period of time that contain messages about social problems that occur in the community such as community empowerment, this is in synergy with the program run by CSR PT KPI RU III Plaju which is implemented in the "Innovative Food Village" program. , has been implemented since 2021 this village is in the Plaju Ulu village, RT.01-06, RW.02, Kec. Plaju, Palembang City. There are five programs that have become innovations from this village, namely; Food Hygine, MPASI Development, Hydroponic Gardens, Tempe Craftsmen WWTP, andPlaju Tempe Center. This study uses a qualitative method which is analyzed using Rogers and Storey's theory in defining the four aspects that become benchmarks for the success of campaign activities. The conclusion of the program is that it has a positive impact on the surrounding community and stakeholders involved both in improving training, community empowerment, and the facilities in the "Innovative Food Village" program so that people are more advanced and productive in utilizing the resources in their surroundings.